2017
DOI: 10.1111/1467-9817.12109
|View full text |Cite
|
Sign up to set email alerts
|

Can earlier literacy skills have a negative impact on future home literacy activities? Evidence from Japanese

Abstract: We examined the cross‐lagged relations between the home literacy environment and literacy skills in Japanese, and whether child's gender, parents' education and child's level of literacy performance moderate the relations. One hundred forty‐two Japanese children were followed from Grades 1 to 2 and assessed on character knowledge, reading fluency and spelling. Their parents responded to a questionnaire assessing the frequency of their teaching and shared reading. Results showed that parent teaching increased a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 41 publications
10
31
0
Order By: Relevance
“…The term "evocative effect" has been used to describe adults' responses to their children's characteristics, such as academic performance or socioemotional responses (Scarr & McCartney, 1983). Previous studies have shown that children's earlier reading skills impact later parental reading-related involvement (e.g., Deng et al, 2015;Inoue, Georgiou, Muroya, Maekawa, & Parrila, 2018;Sénéchal & LeFevre, 2014;Silinskas et al, 2012Silinskas et al, , 2021. For example, Silinskas et al (2012) found that Finnish parents engaged in more frequent teaching of word reading and shared book reading in kindergarten if their children had relatively good early reading skills.…”
mentioning
confidence: 99%
“…The term "evocative effect" has been used to describe adults' responses to their children's characteristics, such as academic performance or socioemotional responses (Scarr & McCartney, 1983). Previous studies have shown that children's earlier reading skills impact later parental reading-related involvement (e.g., Deng et al, 2015;Inoue, Georgiou, Muroya, Maekawa, & Parrila, 2018;Sénéchal & LeFevre, 2014;Silinskas et al, 2012Silinskas et al, , 2021. For example, Silinskas et al (2012) found that Finnish parents engaged in more frequent teaching of word reading and shared book reading in kindergarten if their children had relatively good early reading skills.…”
mentioning
confidence: 99%
“…For instance, parents in some places seem to vary in their perceived importance of developing children’s reading and writing competencies prior to formal school entry, as well as the roles of homes and play in children’s learning ( Lee, 2002 ; Howell et al, 2016 ; Chan, 2012 ). They also reported different frequencies in various formal and informal home learning activities with children ( Kim, 2009 ; Howell et al, 2016 ; Huang et al, 2017 ; Inoue et al, 2018 ; Cheung et al, 2020 ). Though these differing parental beliefs and home practices may be attributed to inexplicable variance, individual differences between participants, and different research methodologies adopted across studies, they may also emerge from variations in cultural values and social situations of different places within the vast region of Asia.…”
Section: Discussionmentioning
confidence: 99%
“…In a low- and middle-income sample in Korea, parents, on average, helped children with homework about three to four times a week, taught children Korean alphabet letters/symbols (Hangul) and literacy and read books with children about once a week, but brought children to the library or bookstore only about once a month ( Kim, 2009 ). In Japan, a study showed that parents taught first graders character/kanji names, word reading and character writing a few times a month, and read to children about 5–30 min per day on average ( Inoue et al, 2018 ). In some places, families tend to prioritize the direct instruction of literacy skills over storybook reading and storytelling, as is the case in samples from Cambodia ( Howell et al, 2016 ) and Indonesia ( Mayasya, 2017 ).…”
Section: What Are the Home Literacy And Numeracy Practices Of Parentsmentioning
confidence: 99%
“…Differential relationships have been identified between reading and the HLE dependent upon when the home environment is assessed, with weaker relationships observed when the HLE is assessed after schooling has begun (Inoue et al, 2018;Krijnen et al, 2020). Whilst previous studies have evaluated contemporaneous associations between spelling and writing and the preschool HLE (Hofslundsengen et al, 2019;Puranik et al, 2018), or longitudinal associations with the school HLE (Guo et al, 2020), the present study will explore relationships between school writing and the earlier preschool HLE.…”
Section: The Present Studymentioning
confidence: 99%
“…Moreover, whilst it may be tempting to conclude that earlier preschool skills have a causal influence on later writing, this interpretation cannot be unambiguously upheld by the current data. Any relationships may be bi-directional with parents altering home experiences in accordance with children's skill levels (Inoue et al, 2018;Kim, 2009).…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%